2006
DOI: 10.1016/s1726-4901(09)70312-0
|View full text |Cite
|
Sign up to set email alerts
|

Spindle Cell Carcinoma of the Oral Cavity and Oropharynx: Factors Affecting Outcome

Abstract: The behavior of SpCC seems to be more aggressive than that of SCC at a similar stage. Setting wider safety margins (> 2 cm) during surgical intervention is suggested. In the case of locoregional recurrence, salvage operation showed some benefit. Seeking an effective chemotherapy protocol is important for the control of distant recurrence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
135
0
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 110 publications
(146 citation statements)
references
References 11 publications
8
135
0
3
Order By: Relevance
“…Sarcomatoid (spindle cell) carcinomas of the head and neck are unusual variants of squamous carcinoma commonly reported in the larynx but also described in other mucosal sites such as gingiva, tongue, hypopharynx and nasal cavity [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17]. These tumors have now been proved to be monoclonal, evolving from conventional squamous carcinoma with dedifferentiation associated with sarcomatoid transformation [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%
“…Sarcomatoid (spindle cell) carcinomas of the head and neck are unusual variants of squamous carcinoma commonly reported in the larynx but also described in other mucosal sites such as gingiva, tongue, hypopharynx and nasal cavity [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17]. These tumors have now been proved to be monoclonal, evolving from conventional squamous carcinoma with dedifferentiation associated with sarcomatoid transformation [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%
“…The larynx is the most frequent site of development in the head and neck region. In the oral cavity, many cases of SPCC in the lips and tongue have been reported, but development of SPCC in the alveolar gingiva is relatively rare [4][5][6][7]. SPCC tends to occur more frequently in men and the onset age varies from the 20s to the 90s, with a reported association with cigarette smoking and alcohol consumption [2, 4-6, 8, 9].…”
Section: Discussionmentioning
confidence: 99%
“…Ellis et al [4] reported metastasis in 16 of 59 cases, with 11 occurrences in the cervical lymph node, and Su et al [5] found a metastasis rate of 33.3%. Survival rates for SPCC of 36% [4] and 27.5% [5] have been reported.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations